Quoting in parliamentary question time: exploring recent change - Reber, Elisabeth (Cambridge University Press, 2021)
"Language change in contemporary English represents a burgeoning field and has primarily been studied from a corpus-linguistic perspective since the mid-1990s (e.g., Hundt and Mair 1999; Leech et al. 2009; Mair 2006; Mair and Leech 2006). Despite relevant article-length investigations on historical recordings from the perspectives of Historical Pragmatics (Jucker and Landert 2015) and Conversation Analysis (Clayman and Heritage 2002a; Clayman et al. 2006, 2007; Heritage and Clayman 2013), as well as the acknowledgement of the need for historical spoken corpora in Interactional Linguistics (e.g., Barth-Weingarten 2014; Couper-Kuhlen 2011), questions of recent change in interactional English have nevertheless remained under-researched to date. Because of the lack of suitable recordings, the historical study of recent change in spoken English was not considered to be a methodologically feasible research direction even as little as a decade ago (e.g., Mair 2006: 21). Against this backdrop, the present study breaks new ground in analysing evolving practices in spoken English (here forms of reported speech) based on authentic recordings from different periods"--
Includes bibliographical references and index
Keywords: Geschichte 1978-2013; Sprachwandel; Zitat; Politische Rede; Englisch